Applications of q-Derivative Operator to the Subclass of Bi-Univalent Functions Involving q-Chebyshev Polynomials. (18th March 2022) - Khan, Bilal; Liu, Zhi-Guo; Shaba, Timilehin Gideon; Araci, Serkan; Khan, Nazar; Khan, Muhammad Ghaffar
Abstract : In recent years, the usage of the q -derivative and symmetric q -derivative operators is significant. In this study, firstly, many known concepts of the q -derivative operator are highlighted and given. We then use the symmetric q -derivative operator and certain q -Chebyshev polynomials to define a new subclass of analytic and bi-univalent functions. For this newly defined functions' classes, a number of coefficient bounds, along with the Fekete–Szegö inequalities, are also given. To validate our results, we give some known consequences in form of remarks.